Evaluation of knowledge, impacts and government intervention strategies during the COVID – 19 pandemic in Nigeria (2020)
The SARS-CoV-2 is a novel strain of coronavirus which is ravaging many countries, and this has become a global public health concern. With the increasing number of COVID-19 confirmed cases and deaths in Nigeria, the pandemic has led to massive public reactions. This data attempted to evaluate the knowledge, impacts, and government intervention during the pandemic. An online survey was conducted using a questionnaire shared via social media using a Snowball sampling technique. The data were analyzed using descriptive statistics and analysis of variance (ANOVA). A total of 387 responses was received. Results show that a significant number of respondents had adequate knowledge about COVID-19 modes of transmission, symptoms, and preventive measures. Respondents maintain personal hygiene as 67% wash their hands with soap. The pandemic has caused worry (65%), anxiety (42%), panic (35%), and depression (16%) among respondents, even as government intervention is seen as inadequate by 70%. There is a need for mental health support and increased information campaigns about COVID-19.